Gray matters architect and designer Eileen Gray - Byrne, Brian ca. 20. Jh (First Run Features, 2014)
"Championed by a new generation of scholars, artists, and collectors, this iconic artist is at last emerging from the dark side as new light is shed on all aspects of the Eileen Gray phenomenon." [imdb.com]
Original: Irland, Monaco, USA, Frankreich, Deutschland, Großbritannien 2014
Keywords: Gray, Eileen -- 1878-1976; Film; DVD-Video